DARK TOURISM AS A SEGMENT OF THE MODERN TOURISM INDUSTRY (INNOVATIVE ECONOMY, 2026)
Mazur V.S.  DARK TOURISM AS A SEGMENT OF THE MODERN TOURISM INDUSTRYPurpose. The aim of the article is to provide a comprehensive analysis of the phenomenon of dark tourism as a component of the modern tourism industry and to substantiate the economic, social, and managerial foundations of its development, taking into account ethical constraints and challenges.Methodology of research. The study employs both general scientific and specialized methods, including: methods of analysis and synthesis to generalize theoretical approaches to defining the essence of dark tourism; the historical and logical method to examine the stages of its formation; comparative analysis to investigate international experience in the functioning of relevant destinations; a systems approach to substantiate the interconnections between economic, social, and ethical aspects of development; and statistical methods to assess the dynamics of tourist flows and the dark tourism market.Findings. The article explores the theoretical foundations and evolution of dark tourism, identifies its main types, motivational factors, and social and cultural functions. It is substantiated that this type of tourism performs not only a recreational function but also educational, memorial, and formative roles, contributing to the development of collective memory and historical consciousness. Global practices of destination functioning, including memorial sites, locations of disasters, and armed conflicts, are analysed, which made it possible to identify different models of memory management. It is established that the effective development of dark tourism requires maintaining a balance between economic benefits and ethical principles, particularly preventing the commodification of tragedies. The problems of developing this segment in Ukraine are outlined, including the imperfection of regulatory and legal support, the lack of systematic management, and the risks of unethical commercialization.Originality. The scientific novelty lies in the deepening of theoretical and methodological approaches to the study of dark tourism as an interdisciplinary phenomenon, as well as in substantiating the concept of forming a model of responsible dark tourism based on the combination of economic efficiency, ethical standards, and social responsibility. Approaches to the classification of destinations and the determination of their functional purpose within the tourism industry system have been improved.Practical value. The practical significance of the obtained results lies in the possibility of their use by public authorities and local self-government bodies in the formation of tourism development policy, the development of regulatory legal acts, and strategies for managing dark tourism destinations. The proposed approaches can be applied by tourism industry stakeholders to implement principles of responsible marketing, as well as in the educational process of higher education institutions in the training of specialists in the field of tourism.Key words: dark tourism, thanatourism, tourist destinations, memorial tourism, economic development, ethical aspects, commodification, tourism management, tourism industry, state regulation.
Keywords: dark tourism; thanatourism; tourist destinations; memorial tourism; economic development; ethical aspects; commodification; tourism management; tourism industry; state regulation